32 Factorial Design of O/W Nanoemulsions of Cholecalciferol Using Box–Behnken Model for Plaque Psoriasis - Sharma, Mukesh Chandra; Sharma, Mukul (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The aim of the study was to design O/W Nanoemulsion using Cholecalciferol in different ratios of surfactants with Box-Behnken design model using Design Expert version 12. Response surface methodology, Box-Behnken was most suited followed by 3 independent variables (A, B, C) and 9 different responses with 17 different batches. Various responses like pH, % drug content drug entrapment and % in vitro drug release at different time intervals comparable with independent variables with % predicted errors calculated with SD±5 values. Materials and Methods: Cholecalciferol used as model drug, SPAN 20, SPAN 80 used as surfactant and Soybean oil used as oil phase for making Nanoemulsion preparation for plaque psoriasis treatment prepared by probe sonication method. Results: The VIF values were 1.0-1.03 and Ri2 range between 0.00-0.0058 means correlated with each-others were in range, showed statistically correct and chances of error is minimum shown in Table 1. The predicted pH 7.79±0.38, Drug entrapment 92.68±4.67 and % Drug content was found to be 92.5±6.08 while experimental values were 7.20±0.11, 95.32±0.76, 93.29±1.15%. The predicted values of in vitro drug release were 5.54±1.57, 13.98±2.19, 25.96±4.40, 47.14±3.18, 68.17±6.02, 80.36±4.39% while experimental values were 8.50±0.50, 16.54±2.30, 29.54±2.27, 42.20±1.10, 68.54±1.27, 79.64±2.35% at 10, 30, 60, 90, 120, 210 min respectively see Table 2. The p values was <0.0001. Conclusion: The model showed F-values were in the range 0.28-5.08 showed non-significant while p-values was 0.028 showed significant values followed quadratic model. This showed that the model is best suitable for optimization.
Keywords: Optimization; Nanoemulsion; Box-Behnken design; Psoriasis; 32 factorial designs